Model Pembelajaran Kooperatif Two Stay Two Stray untuk Meningkatkan Pemahaman Konsep Pola Bilangan Siswa SMP - Dini Yusmika; Mailizar Mailizar; Bainuddin Yani (Universitas Syiah Kuala, 2020)
Students must understand mathematical concepts. However, the observations revealed a lack of students' understanding of mathematical concepts because learning conditions remain conventional. The teacher is dominant in conveying information, and students only memorize concepts in the form of formulas without understanding. The Two Stay Two Stray model can increase the understanding of these concepts. This model is applied to the topic of number patterns. This study aimed to examine the achievement of students' minimum criteria of mastery learning (known as KKM in Indonesia)and their improvement in understanding the concept after implementing the model in Year 8 at one of the junior high schools in Aceh Besar, Indonesia. This research is quasi-experiment type using pre-test and post-test. This study selected the population of all Year 8 students of the school studied, and the sample was 20 Year 8 students. Data collection involved giving five short answer questions during the pre-test and post-test. The data were analyzed using the Gain Score and t-test. The results concluded that students could achieve the KKM, and their understanding of the concept was increased to the medium category.